Analysis of Tuberculosis Control (Case Study in The City of Mojokerto) Year 2024 - Yahya, Mokhamad Suyono; Setiaji, Bambang (Syntax Literate, 2024)
This study aims to analyze the tuberculosis (TB) situation in Mojokerto City, focusing on the increase in cases among children and identifying effective countermeasures. TB, a preventable and curable infectious disease caused by Mycobacterium tuberculosis, is particularly problematic in developing countries like Indonesia due to high incidence and mortality rates, necessitating a comprehensive control strategy. Employing qualitative methods, this research delves into the practices, perceptions, and social dynamics affecting TB control efforts in Mojokerto, illuminated by the latest data showing a significant increase in pediatric TB cases and the public health situation. Findings reveal a TB incidence rate of 385 per 100,000 inhabitants, a case detection rate of 75%, and a notably high pediatric TB case proportion of 32%. The effectiveness of case tracking by health centers varies, with an average of only 54% receiving Tuberculosis Preventive Therapy (TPT). Major obstacles include limited access to radiology services, social stigma, and the need for adequate health facilities. Innovations such as the "Mbak Desi Fights TB" program and enhanced cross-sector cooperation are deemed crucial to strengthen control strategies. The study concludes that a multifaceted strategy is essential for combating TB in Mojokerto, which should include enhanced case detection, health system strengthening, and community integration in control efforts. Increased collaboration across sectors and advancements in research and development are expected to accelerate TB elimination. This research offers efficient recommendations to improve TB control strategies, based on an in-depth analysis of the current conditions and social dynamics in Mojokerto.